Geothermal Stamps of Iceland - Lund, John W. (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1996)
Iceland, a leader in the use of geothermal energy, is also a leader in issuing stamps depicting various geothermal manifestations such as geysers, volcanic eruptions and methods of utilizing the energy. In my recent visit to Iceland as the visiting lecturer for the UNU geothermal program, I was able to collect some of the more current issues. A review of the older issues and most of the new ones are described and shown